Implementasi Sistem Informasi Pendataan Warga Berbasis Website (Studi Kasus: Perumahan Villa Mutiara Gading 1 RW 18) - Sarimole, Frencis Matheos; Azis, Abd; Raihanah, Syifa; Rahmah, Shafira Azzahra Nurul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to implement an efficient Web-Based Information System in collecting data on residents at the Villa Mutiara Gading 1 RW 18 Setia Asih Housing Complex, Tarumajaya, Bekasi Regency. As the digitalization era continues to develop, efficient management of citizen data has become very important in meeting the needs of modern society. The system development method used is a prototype development approach. which involves several stages, namely listening to user needs, building or improving a prototype, and testing the prototype. Various integrated features, such as recording citizen data, financial administration, and announcements, are focused on RW18. The implementation results show an increase in community services, a positive impact on environmental management, as well as increased interaction between RW 18 members and residents. With this system, recording citizen data becomes more efficient, financial administration is organized, and RW18 information can be easily accessed by all residents. The approach used in this research supports the development of a system that is responsive to user needs and can provide significant benefits to society.